Age and nationality in relation to injuries at sea among officers and non-officers: a study based on contacts from ships to Telemedical Assistance Service in Denmark - Kimmo Herttua; Stine Gerdøe-Kristensen; Jan C Vork; Jesper Bo Nielsen (BMJ Open)
Objectives Characterisation of worker injuries on board merchant ships is modest. Using telemedical service contacts in Denmark, we describe the worker injuries patterns and factors related to injury incidence.Methods The data for this study were based on contacts (n=1401) from ships to Telemedical Assistance Service (TMAS) in Denmark in 2004–2014, which were supplemented with data on the annual estimation of all seafarers from the Danish Maritime Authority (n=73 336). The final data included information on broad age groups, occupation and nationality. The outcomes were injuries from any cause and six broad categories of injuries characterised by anatomic location or type of injury.Results During the observation period of 11 years, there were 1401 contacts to TMAS due to injuries, of which 36% were in upper limb, 18% in lower limb and 13% in the head. Age-adjusted incidence rates for all injuries varied between 13.6 and 26.8 incidences per 1000 person-years in 2004–2014. In most types of injuries, younger and older seafarers had higher risk for injuries than seafarers aged 30–49 years. Depending on the type of injury, non-officers had threefold to fivefold increased odds of injuries compared with officers, the risk being highest for head injuries with an OR of 5.00 (95% CI 3.19 to 7.83). Non-officers from the European Union (EU) had higher risk in most types of injuries than non-officers from outside the EU, whereas the pattern of this risk was inverse among officers.Conclusions These findings suggest that non-officers and European seafarers have an increased risk for several types of injuries on board Danish-flagged merchant ships. Additionally, age affected risk with the younger (<30 years) and older (>50 years) seafarers having increased risk.